Continental-Scale Network Reveals Cross-Jurisdictional Movements of Sympatric Sharks With Implications for Assessment and Management - Huveneers, Charlie; Niella, Yuri; Drew, Michael; McAuley, Rory; Butcher, Paul; Peddemors, Victor; Waltrick, Daniela; Dowling, Chris; Mountford, Silas; Keay, Ian; Braccini, Matias (Frontiers in Marine Science, 2021)
Understanding the movement ecology of marine species and connectivity of populations is required for effective fisheries management. This is especially the case for species with wide-ranging distributions for which movement can span across several jurisdictions with different management regulations. We used the Australian national network of acoustic receivers facilitated by the Integrated Marine Observing System (IMOS) to describe the extent and frequency of movements for two large epipelagic shark species, the bronze whaler (C. brachyurus) and dusky shark (Carcharhinus obscurus). A total of 210 sharks (117 bronze whalers and 93 dusky sharks) were tracked for a 10-year period during which 21% and 9% of detected bronze whalers and dusky sharks, respectively, moved between Australian states. Bronze whalers showed more variable inter-state movements, mostly between Western Australia and South Australia but also eastwards to New South Wales (NSW). Although no dusky sharks tagged in Western Australia undertook inter-state movements, ~50% of the sharks tagged in South Australia went to Western Australia. Five dusky sharks tagged in NSW were detected across different states but remained on the east and southeast coast (Queensland, NSW, Victoria, and Tasmania). The IMOS receivers also detected six bronze whalers in Ningaloo Reef, representing an extension of the previously known Australian distribution. Our findings highlight the value of collaboration between researchers and the value of national infrastructure, by providing a more accurate understanding of inter-state movements. This new information will allow the development of more adequate population dynamics models for stock assessment and management advice, requiring collaboration among state agencies for coordinating research activities, sharing data and resources, and establishing appropriate cross-jurisdictional policies which are essential for achieving successful management and conservation outcomes for highly migratory species.